Relationships Between Self‐Reported and Observed Parenting Behaviour, Adolescent Disordered Eating Attitudes and Behaviours, and the 5‐HTTLPR Polymorphism: Data From the Australian Temperament Project. (10th July 2017) - Rozenblat, Vanja; Ryan, Joanne; Wertheim, Eleanor; King, Ross; Olsson, Craig A.; Letcher, Primrose; Krug, Isabel
Abstract: This study examined whether self‐reported and observationally measured parental behaviours were associated with disordered eating, and investigated possible moderation by a serotonin‐transporter polymorphism ( 5‐HTTLPR ). Study 1 included 650 adolescents from the Australian Temperament Project who completed the Eating Disorder Inventory‐2 Drive for Thinness and Bulimia scales at 15/16 years and were genotyped for 5‐HTTLPR . Parents completed an Australian Temperament Project‐devised measure of parental warmth and harsh punishment. Study 2 included a subgroup of 304 participants who also engaged in a video‐recorded family interaction, with observed parental warmth and hostility coded by the Iowa Family Interaction Rating Scale. Greater self‐reported parental warmth was associated with lower bulimia scores. Conversely, observationally measured parental warmth was associated with lower drive for thinness, but not bulimia. Self‐reported parental harsh punishment was associated with bulimia only, with observed parental hostility associated with neither outcome. 5‐HTTLPR genotype did not moderate the relationship between parent behaviours and adolescent disordered eating. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.